Increasing Students' Learning Impact on Thematic Learning Theme 8 Through Using Integrated Types of Webbed Learning For Elementary School Students - Lani Elianti; Agusalim Agusalim; Mitrakasih La Ode Onde (Institute Journal and Publication Muhammadiyah University of Buton, 2023)
The aim of the analysis is to increase the learning impact of students in thematic learning theme 8 by using a webbed-style integrated learning type for class III students at SD Negeri 1 Kambowa. The research method includes research procedures, namely classroom action research (PTK) which consists of planning, implementation, observation and reflection. The topic of analysis is class III students, a total of 20 students, including 9 male students and 11 female students. The method of combining information used is through examination, observation and archiving. This analysis was carried out in the even semester of the 2021/2022 academic year in two cycles, each cycle taking place per two meetings. The impact of student learning in the pre-cycle before implementing the webbed type integrated learning model was that there were 7 students who finished training themselves with 35℅ classical completeness. After implementing the webbed type integrated learning model in cycle I, there were 14 students who completed the study with a classical completeness of 70℅. Then in cycle II it increased to 17 students who completed their studies with a classical completeness of 85℅. Based on the research results, it can be concluded that using the webbed type integrated learning model can improve student learning outcomes in the thematic study of theme 8 of class III students at SD Negeri 1 Kambowa.